1996
DOI: 10.1302/0301-620x.78b2.0780195
|View full text |Cite
|
Sign up to set email alerts
|

The Cementless Pm Hip Arthroplasty

Abstract: We implanted 300 uncoated cementless PM prostheses into 271 patients and followed 251 (92.6%) of them for four to seven years. By then 37 had already been revised for aseptic and three for septic loosening. The survival rate with implant failure as the endpoint was 88.8% for the cup and 85.3% for the stem after six years. There was a higher risk of implant loosening in congenital dysplasia, unilateral hip arthroplasty and obesity. The results of 225 unrevised hip replacements were assessed by questionnaire. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
1
19
0
3
Order By: Relevance
“…Considering that Onsten evaluated cemented implants, the effect of body [5][6][7][8][9][10]. Other, studies have indicated that a high BMI is linked with stem loosening [22] and a poor clinical outcome [23]. Moreover it has been reported that each additional BMI unit increases the risk of loosening [4].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Onsten evaluated cemented implants, the effect of body [5][6][7][8][9][10]. Other, studies have indicated that a high BMI is linked with stem loosening [22] and a poor clinical outcome [23]. Moreover it has been reported that each additional BMI unit increases the risk of loosening [4].…”
Section: Discussionmentioning
confidence: 99%
“…Excellent long-term results are known for some cemented stems [1,4]. On the other hand, implantation without cement may have some benefits and increasing interest in uncemented hip replacement is reflected in a high number of recent publications [3,5,6,22].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the system was used in more than 60,000 patients. After good early results (Parhofer and Ungethum 1984, Krodel and Refior 1988, Wolf et al 1988, the mid-term results turned out to be moderate at best (Reichelt and Botterer 1993, Dickob and Martini 1996, Karches et al 1996) with a 6-year survival rate of 88%.…”
mentioning
confidence: 99%